Politische Erfahrungen bei der wirtschaftlichen und gesellschaftlichen Transformation; Political experience in economic and social transformation - Christoph Bergner (Wirtschaftsdienst, 2021)
Der deutsche Vereinigungsprozess wird aus verschiedenen Perspektiven unterschiedlich beurteilt. Die Darstellungen reichen von kaum vorstellbaren Erfolgen bis bin zu einer Traumatisierung der Bevölkerung der östlichen Bundesländer. Sechs Thesen sollen die gesellschaftliche und wirtschaftliche Transformation im Zuge der deutschen Vereinigung verdeutlichen. – – This article outlines the political events related to German unification on the occasion of its 30th anniversary. The revolutionary upheaval of 1989-90 led to the formulation of common economic and social models in the former Eastern bloc countries. The implementation of these transformation goals proved difficult in former socialist countries and met with little success. It became apparent that the political challenges of transforming centrally planned socialist economies into market economies governed by the rule of law were largely underestimated by politicians. In East Germany, the Treuhandanstalt (privatisation agency) made an indispensable, albeit highly conflictual, contribution to solving this problem. The economic and social transformation of East Germany took place with its accession to the German Constitution. The fall of the 'Iron Curtain' gave the process of globalisation a considerable acceleration, which in turn made strengthening competitiveness a growing challenge for German politics.
Keywords: O10; R11; 330